Implementation of a tax and one hundred per cent dividend scheme as a means for New Zealand to address greenhouse gas emissions - Revell, Laura (New Zealand Science Review, 2011)
​Climate scientist Dr James Hansen, director of NASA’s Goddard Institute for Space Studies, visited New Zealand in May 2011 to address the New Zealand public on climate change. As well as speaking about the scientific basis for the detection and attribution of changes in climate and potential impacts of climate change, Dr Hansen advocated the use of a tax and dividend scheme for reducing CO2 emissions (Hansen 2011). New Zealand aims to meet its greenhouse gas emissions reduction targets via an emissions trading scheme (ETS). While the ETS has built strong political momentum, there is also value in discussing potential alternatives, such as that advocated by Dr Hansen, to explore whether such a scheme could be applicable in the New Zealand context.